Challenges in Academic English Writing: Evidence from Kazakhstani EMI University - Tulepova, Saule; Bekturova, Madina; Kassymova, Gulnara; Gaipov, Davronzhon (Journal of Qualitative Research in Education, 2025)
This small-scale research explores the most challenging aspects of the Academic English Writing course experienced by undergraduate students of the Teaching English as a Foreign Language (TEFL) program within an English-Medium Instruction (EMI) university in Kazakhstan. The study aims to identify the students' difficulties in academic writing and describe key factors contributing to them as well as to develop evidence-based recommendations for improving course design and delivery. Data were collected through a semi-structured questionnaire, which combined multiple-choice and open-ended items addressing students' perceived challenges and underlying causes related to writing structure, coherence, argumentation, and source integration. In addition, the academic writing instructors were interviewed to elicit information on the strategies they used to develop the students' academic literacy. Quantitative data were analyzed using SPSS, version 20, while qualitative responses were examined thematically to capture teachers' perspectives and suggestions for course enhancement. The findings reveal recurrent challenges in critical thinking, academic vocabulary use, and adherence to academic conventions—issues that are often intensified by the EMI context and limited prior exposure to academic discourse in English. Teachers similarly emphasize the need for earlier and extended writing instruction, integration of practical assignments, and adaptive pedagogical approaches to meet EMI students' academic and professional needs. Based on the results, practical recommendations are proposed for writing instructors, curriculum developers, and program coordinators to strengthen academic writing support within EMI-based teacher education programs.